(untitled) (Revista Científica Ciencias Naturales y Ambientales, 2015)
The goal of this research is to determine the halotolerance and enzymatic synthesis of Pseudomonas cf. fluorescens. To evaluate halotolerance, cell growth was quantified in 2 M, 3 M and 4 M NaCl at 30°C. Also, the extracellular proteolytic enzyme synthesis, amylolytic and lipolytic was evaluated by halos of production. The treatment of 4 M to 30°C was the best Halotolerance assay, with a growth rate (μ) 0.048 h-1, doubling time (td) 14.55 h and a cell density of 5 906 666 ± 305 505 cell/mL. Proteolytic synthesis was the highest (halo 30 ± 0.82 mm), followed by the production of amylases (halo of 22.5±1.73 mm), the lipolytic activity was not observed.